On scheduling algorithm for device-to-device communication in 60 GHz networks - ur Rehman, Waheed; Jiang Han; Chengcheng Yang; Ahmed, Manzoor; Xiaofeng Tao (IEEE Wireless Communications and Networking Conference : [proceedings] : WCNC, 2014)
The world is witnessing a tremendous increase in data demands which is subject to the new emerging technologies, applications and services. 60 GHz communication network is one of such technology, claiming data rate in multi-gigabits. In this paper, we propose a scheduling algorithm for device-to-device 60 GHz network having directional antennas. The proposed algorithm utilizes the vertex coloring scheme and is optimized to improve system throughput. A threshold minimum distance between conflicting flows is used to keep the accumulative interference limited. Also, when there are conflicts among different flows, those with better data rate prospects will be scheduled priorly. Simulation results show that our scheme has brought significant improvement to system throughput almost by 19% and average flow number per slot is improved by 12%, as compared to other scheduling algorithms.